2018
DOI: 10.1016/j.clinph.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A new criterion for detection of radiculopathy based on motor evoked potentials and intraoperative nerve root monitoring

Abstract: The criterion of decrease of the MEP area has a higher reliability and accuracy in the detection of intraoperative radicular lesions than the amplitude reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Additionally, if SSEP and EMG are monitored at the same time, SSEP interferes with EMG, making the EMG results difficult to interpret. Therefore, studies have suggested combining MEP and EMG to monitor lumbar surgery [ 6 , 29 , 36 38 ], but in our study, there was one case with only SSEP changing, resulting in the development of numbness and tingling in the anterior thighs. These results suggest that monitoring with SSEP better monitors the sensory function of the nervous system during surgery.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Additionally, if SSEP and EMG are monitored at the same time, SSEP interferes with EMG, making the EMG results difficult to interpret. Therefore, studies have suggested combining MEP and EMG to monitor lumbar surgery [ 6 , 29 , 36 38 ], but in our study, there was one case with only SSEP changing, resulting in the development of numbness and tingling in the anterior thighs. These results suggest that monitoring with SSEP better monitors the sensory function of the nervous system during surgery.…”
Section: Discussionmentioning
confidence: 71%
“…The alarm standard set by our research included an amplitude drop greater than 80%, and some were greater than 50% [ 28 ]. Moreover, a 70% decrease in the MEP area was previously used as a criterion for warning in IONM [ 29 ]. However, which standard should be used for endoscopic lumbar inter-body fusion surgery requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Число ложноположительных результатов достаточно велико, что ставит под сомнение достоверность принятых в нейрофизиологическом сообществе критериев [5]. По наблюдениям зарубежных авторов, в ряде случаев при оперативных вмешательствах у пациентов с цервикальной миелопатией при падении амплитуды МВП на 80 % не наблюдалось неврологического дефицита в послеоперационном периоде, что говорит о низкой информативности данной модальности как предиктора развития неврологического дефицита [6,7].…”
Section: Introductionunclassified